Apakah Slack Anggaran Mampu Mengukur Efisiensi dan Efektivitas Organisasi Pada Industri Jasa Kesehatan di Indonesia? (Journal of Hospital Management, 2019)
Issues of financial performance that are not in accordance with the budget will affect the investment activities for the rejuvenation of new medical devices. In addition, the intense competition in health services business today can threaten the survival of hospitals if the financial performance of hospitals continues to decrease because it does not compatible with the budgets. The purpose of this study is to provide empirical evidence that there is a simultaneous process of the influence of budgetary participation, organizational commitment, and budgetary slack, on Financial Performance. The research design used is quantitative with the type of hypothesis testing. This type of research is causality. The unit of analysis is all employees. The time horizon is a one-shot study. This research uses Structural Equation Modeling (SEM) and samples that have been collected around 122 questionnaires through sampling technique is saturated sampling. By using AMOS software, it can be concluded that Budget Participation, Organizational Commitment and Budget Slack has a positive and significant effect on Financial Performance. Budget Participation has a significant negative effect on Budget Slack, Organizational Commitment has no significant negative effect on Budget Slack, budget participation has a significant positive effect on financial performance, organizational commitment has a significant positive effect on financial performance, and budget slack has a significant positive effect on financial performance. The research findings show that there is a Budget Slack caused by manipulative behavior with low integrity so that hospital financial performance is not achieved. Keywords: Budget Participation, Organizational Commitment, Budget Slack, Financial Performance